2013
DOI: 10.1007/s11414-013-9324-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Successful Treatment Outcomes Among a Sample of Urban American Indians/Alaska Natives: the Role of Social Environments

Abstract: Very few studies have analyzed the role of social environments on substance abuse treatment outcomes among urban American Indians/Alaska Natives (AI/ANs). This study examined a measure of positive treatment response—abstinence from substance use at treatment discharge—among urban AI/ANs in Los Angeles County. The sample included all AI/ANs in outpatient drug-free (e.g., no methadone) treatment and residential treatment from 2004–2008 (N = 811). Predictors of abstinence at discharge were (a) having recovery-ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This was evident in the prominent use of group recovery resources by both AI and non-AI PPW. Both found it helpful to interact with others who shared their experience of struggling to maintain sobriety, a theme consistent with prior research indicating the importance of recovery oriented social support (Spear et al 2013; Chong & Lopez 2008). Beyond this need, our findings indicate the importance of positive role models successful at maintaining sobriety.…”
Section: Discussionsupporting
confidence: 80%
“…This was evident in the prominent use of group recovery resources by both AI and non-AI PPW. Both found it helpful to interact with others who shared their experience of struggling to maintain sobriety, a theme consistent with prior research indicating the importance of recovery oriented social support (Spear et al 2013; Chong & Lopez 2008). Beyond this need, our findings indicate the importance of positive role models successful at maintaining sobriety.…”
Section: Discussionsupporting
confidence: 80%
“…Take the one-sample studies first. The Forest plot suggested differences between Kunic [25] studies and the rest of the one-sample studies. Kunic [25] measured the percent of participants testing positive for drugs and alcohol, whereas the other studies used self-reported of consumption.…”
Section: Discussionmentioning
confidence: 94%
“…The Forest plot suggested differences between Kunic [25] studies and the rest of the one-sample studies. Kunic [25] measured the percent of participants testing positive for drugs and alcohol, whereas the other studies used self-reported of consumption. We used this difference as a moderator for the observed heterogeneity in effect sizes, which was significant Qm (1) = 56.94, p < .001.…”
Section: Discussionmentioning
confidence: 94%
“…While these efforts have been successful in decreasing risk for AEP, the inclusion of social support has the potential to further improve initiating and sustaining any behavioral change. For example, American Indian patients in residential treatment who reported high levels of social support had nearly three times the odds of abstaining from substance use than did AI who had lower social support levels thirty days after discharge [33]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, being surrounding by family and peers who use alcohol or other drugs predicted relapse for American Indian women following discharge from residential treatment [32]. Conversely, American Indian patients from residential treatment who reported high levels of social support had nearly three times the odds of abstaining from substance use than did American Indian patients who had lower social support levels [33]. …”
Section: Introductionmentioning
confidence: 99%